Study on the Characteristics of Modern Urban Planning and Construction in Tangshan - Xu, Yang; Yin, Hu; Wang, Lei (Journal of Social Science and Humanities, 2025)
Tangshan is an industrial and mining city that rose rapidly in the modern period due to the development of the foreign affairs movement. This paper systematically organizes and summarizes historical materials related to the construction of urban space in modern Tangshan through literature reviews, field research, and interviews. It divides the process of Tangshan’s urban construction into three historical periods, categorizes the main construction contents of each phase, and maps them spatially by integrating historical records and base maps. The characteristics of Tangshan’s urban construction in these three historical periods are analyzed. On this basis, starting from the method of modern urban planning theory, we analyze the main factors affecting the rapid development of Tangshan from a small village to a famous heavy industrial city in North China, and summarize the planning ideas embodied in the process of mapping out the modernization of Tangshan that are different from the traditional urban planning theories, in an effort to provide a reference for the modern research on the synergistic development of Beijing-Tianjin-Hebei, and also seek to learn from the history and to provide a reference for the resource-based cities, the It also seeks to draw lessons from history for the study of the transformation and development path of resource-oriented cities, especially resource-oriented shrinking cities.